Patriotic theme in Hugh Macdiarmid's creative heritage - Лемещенко-Лагода, Вікторія Володимирівна; Лемещенко-Лагода, Виктория Владимировна; Lemeshchenko-Lagoda, Viktoriia (МГПУ, 2012)
UK: Стаття присвячена патріотичній тематиці у творчій спадщині Х'ю Макдерміда. Мета статті - показати, як авторський патріотизм впливає на його творчість, та довести, що патріотична тематика с домінантною у творах X ’ю Макдерміда. RU: Статья посвящена патриотической теме в творческом наследии Хью Макдермида. Цель — показать, как авторский патриотизм влияет на его творчество, и доказать, что патриотическая тематика является доминантной в произведениях Хью Макдермида. EN: The article is devoted to the patriotic theme in the Hugh MacDiarmid creative heritage. The aim is to show how the author patriotism influences his creative work, and to prove that patriotic theme is the dominant theme in the MacDiarmid’s works.
Keywords: патріотична тематика; мова Скотс-Лалланс; шотландська література; патриотическая тематика; язык Скотс-Лалланс; шотландская литература; patriotic theme; language Scots-Lallans; Scottish literature